Composite spinel-corundum refractory material for crematorium and preparation method thereof
By using ferromanganese alloy and alumina at high temperature firing under buried carbon atmosphere, the problems of unsatisfactory performance and short service life of existing refractory materials are solved, and a high-efficiency synthetic composite spinel-corrugated refractory materials are achieved, with high strength, good thermal shock stability and good corrosion resistance.
Patent Information
- Application Number
- CN202410829679.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The existing refractory materials for cremator have problems such as poor performance and short service life. When iron oxide and manganese oxide are used as raw materials to synthesize iron aluminum spinel and manganese aluminum spinel, Fe/Mn ion valence, high temperature required for solid phase sintering, and long reaction time.
Using manganese ferroalloy and alumina as raw materials, high-temperature sintering is carried out under buried carbon atmosphere, and the MnO/FeO@Mn-Fe core-shell structure is built through the liquid phase sintering structure to generate a composite spinel-corundum refractory material.
The prepared composite spinel-corundum refractory material has high strength, good thermal shock stability and good corrosion resistance. It is suitable for high-tech crematoriums, extending service life and reducing production costs.
Smart Images

Figure CN118851733B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a composite spinel-corundum refractory material for a crematorium and a preparation method thereof. Background Art
[0002] The biggest feature of the ash-picking cremator is that the cremation is more civilized. It can realize one car, one furnace, and one corpse. In the process of cremation, there is no need to use other tools to turn the corpse, and the ashes will not be mixed. The ash-picking cremator usually has a main combustion chamber and a reburning chamber, which can achieve the full combustion of toxic and harmful gases and greatly reduce pollutant emissions. In the process of cremation of the body in the crematorium, the types of combustibles are complex, including bodies, relics, coffins, etc. The fuel supply is constantly adjusted, and the furnace door needs to be opened and closed many times during the cremation process, resulting in large fluctuations in the combustion conditions in the furnace. At the same time, due to the particularity of cremation of the body, the kang surface of the ash-picking cremator is eroded by high-temperature flames and acidic body fluids during operation. After the cremation is completed, the kang surface will cool down suddenly. The kang surface is very easy to peel off and crack, resulting in a short service life of the crematorium kang surface. At present, the lining and kang surface of the crematorium are mainly made of clay and high-alumina refractory materials. After 4 to 5 months of use, the kang surface materials must be completely replaced or overhauled, which seriously affects the normal operation of the crematorium. Frequent replacement of the kang surface also increases the operating costs of the funeral home. The lining of the crematorium is also prone to cracking and peeling due to high-temperature weathering and other reasons. The cracks in the kang surface after cracking are very likely to cause the penetration and accumulation of corpse oil. The corpse oil will continue to burn and produce odor during the cooling process of the kang surface after exiting the furnace, which seriously damages the quality of the working environment and endangers the physical and mental health of employees. With the advancement of cremation technology, refractory materials for cremators must adapt to the development requirements of green, environmental protection, and longevity. The development of high thermal stability and high-strength furnace bricks is imperative; and the development of ash-picking cremators has an even more urgent demand for kang surface refractory materials with better thermal shock resistance and corrosion resistance.
[0003] In the 1990s, RHI first proposed the use of iron aluminum spinel (FeAl2O4) as a refractory raw material. Iron aluminum spinel belongs to the equiaxed crystal system with a volume density of 4.38g / cm 3 , hardness 7.5, melting point 1780℃, thermal expansion coefficient 8.2~9.0×10 -6 ℃ -1 The Fe in ferroaluminum spinel is +2. When synthesizing ferroaluminum spinel, it is necessary to ensure that Fe 2+The iron-aluminum spinel currently used in industry is mostly synthesized by RHI using the electrofusion method. However, the electrofusion method consumes a lot of energy and the price of iron-aluminum spinel raw materials is high. Therefore, many researchers are exploring how to use low-cost methods to synthesize iron-aluminum spinel. When synthesizing iron-aluminum spinel by sintering, a certain reducing atmosphere must be ensured, otherwise Fe will exist in the +3 form. Therefore, it is currently difficult to synthesize iron-aluminum spinel by sintering in industry.
[0004] In recent years, manganese aluminum spinel (MnAl2O4) as a new type of spinel, due to its high melting point (1850℃), low thermal expansion coefficient ((8.5~9.5)×10 -6 ℃ -1 ), good structural flexibility and corrosion resistance and other excellent properties have been widely used in industry. Especially as a high-temperature refractory material, due to its high thermal shock resistance and good kiln skin resistance, it has successfully replaced traditional magnesia-chrome bricks and applied to cement rotary kiln firing zone. In addition, it also has important applications in the bottom and side walls of the ladle in the steel industry, the checkerboard bricks in the heat storage chamber of the glass furnace, etc. At present, the synthesis methods of manganese aluminum spinel mainly include solid-phase sintering method, sol-gel method, plasma fusion method, etc. When manganese aluminum spinel is synthesized by solid-phase sintering reaction using oxide as raw material, it is difficult to synthesize high-purity manganese aluminum spinel due to the change of the valence state of Mn ions; the sol-gel method has a long synthesis time and high cost, and is not suitable for industrial production; the plasma fusion method has high energy consumption and high cost. Summary of the invention
[0005] The purpose of the present invention is to provide a composite spinel-corundum refractory material for crematorium and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art. The refractory material of the present invention can overcome the problems of the existing refractory materials such as unsatisfactory performance and short service life, and can also overcome the problems of Fe / Mn ion valence change, high temperature required for solid phase sintering, long reaction time, etc. existing in the prior art when iron oxide and manganese oxide are used as iron source / manganese source to synthesize iron aluminum spinel and manganese aluminum spinel materials.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a composite spinel-corundum refractory material for a crematorium, which comprises the following raw materials by mass percentage: 80-95% of alumina and 5-20% of ferromanganese alloy.
[0008] Furthermore, the alumina is composed of alumina aggregate and activated alumina powder; the particle size of the alumina aggregate is greater than 0 mm and less than or equal to 3 mm.
[0009] Furthermore, in terms of mass percentage, the alumina aggregate accounts for 55-70%, and the activated alumina powder accounts for 30-45%.
[0010] Furthermore, the alumina aggregate is composed of alumina with a particle size of 1mm<≤3mm and a particle size of 0<≤1mm; the mass ratio of the alumina with a particle size of 1mm<≤3mm and a particle size of 0<≤1mm is (50-55):(5-15).
[0011] Furthermore, the particle size of the ferromanganese alloy is ≤100 μm.
[0012] The second technical solution of the present invention is a method for preparing the composite spinel-corundum refractory material for the crematorium, comprising the following steps:
[0013] Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick blank;
[0014] The bricks are dried and then fired at high temperature to obtain the composite spinel-corundum refractory material for the crematorium.
[0015] Furthermore, the drying specifically includes: drying until the residual moisture of the brick is less than 1.5wt.%; the drying temperature is 50-150°C and the drying time is 10-48h.
[0016] Furthermore, the high temperature sintering is carried out under the condition of carbon-buried atmosphere; the equipment used for the high temperature sintering is a tunnel kiln or a shuttle kiln;
[0017] The high temperature sintering temperature is 1600-1750° C. and the time is 5-15 hours.
[0018] The third technical solution of the present invention: an application of the above-mentioned composite spinel-corundum refractory material for crematorium in the preparation of crematorium.
[0019] Both iron-aluminum spinel and manganese-aluminum spinel have high melting points and low thermal expansion coefficients. Iron-aluminum spinel has excellent resistance to alkaline medium erosion, and manganese-aluminum spinel has good structural flexibility and thermal shock resistance. Introducing the two as composite reinforcement phases into the corundum matrix can obtain a long-life refractory material for crematoriums with excellent high-temperature strength, thermal shock resistance and erosion resistance.
[0020] The existing technology generally uses FeO and MnO oxides as raw materials to prepare iron aluminum spinel and manganese aluminum spinel by solid phase sintering, but there is Fe 2+ and Mn 2+The valence state is difficult to control, the sintering temperature is high, the reaction time is long, etc. However, this application uses manganese iron alloy as raw material, introduces finely dispersed, highly active MnO and FeO microcrystals in situ, and constructs a material with iron aluminum spinel and manganese aluminum spinel composite reinforcement (composite spinel-corundum refractory material for crematorium, with MnO / FeO@Mn-Fe core-shell structure) through liquid phase sintering, and also solves the problems existing in the preparation of iron aluminum spinel and manganese aluminum spinel using FeO and MnO oxides as raw materials.
[0021] During the high temperature sintering process, under the condition of low oxygen partial pressure of air carbon embedding (carbon embedding atmosphere condition), as the temperature rises, the surface of the manganese-iron alloy powder particles undergoes oxidation reaction (Formula (1)), generating MnO and FeO coating layers (FeO and MnO coated manganese-iron alloy core-shell structure). As the temperature further rises to about 1550°C and above (above the melting point of Mn-Fe alloy), the Mn-Fe alloy melts (see Figure 2 ). Under the action of thermal stress, the MnO and FeO coatings on the particle surface break (i.e., the core-shell structure breaks under the action of thermal stress), forming several finely dispersed, highly active submicron MnO and FeO grains, which greatly reduce the temperature required for the reaction with Al2O3 to form iron-aluminum spinel and manganese-aluminum spinel, and improve the reaction efficiency; the Mn-Fe alloy liquid phase inside the particle overflows and forms a Mn-Fe-C melt with the C on the particle surface; the MnO and FeO microcrystals migrate along the structural pores under the influence of the Mn-Fe-C melt. On the one hand, the dissolution of C in the Mn-Fe alloy greatly improves its wettability to alumina particles, allowing MnO, FeO and Al2O3 to form good physical contact. The Mn-Fe-C melt provides a fast channel for ion diffusion between MnO, FeO and Al2O3, transforming traditional solid-phase sintering into liquid-phase sintering. At the same time, the newly formed MnO and FeO crystallites have extremely high reactivity, which can greatly reduce the temperature required for spinel formation and improve reaction efficiency. On the other hand, the presence of a strong reducing medium in the Mn-Fe-C alloy melt can effectively regulate the oxygen partial pressure inside the material to a low value range, making Fe 2+ and Mn 2+ Stable existence, avoiding the change of Fe / Mn ion valence and reducing the synthesis efficiency of spinel. In summary, as the temperature rises to above 1550℃, the FeO / MnO-coated Mn-Fe alloy particles gradually break, and under the action of the Mn-Fe-C liquid phase, the newly formed MnO and FeO crystallites react with the Al2O3 particles (Formula (2), Formula (3)) to generate manganese aluminum spinel and iron aluminum spinel reinforcement phases, and finally obtain the composite spinel-corundum refractory material for crematorium.
[0022] Mn-Fe(alloy,S>MnO(s)+FeO(s)+C(s)(1)
[0023]
[0024] The present invention discloses the following technical effects:
[0025] (1) The composite spinel-corundum refractory material for crematorium of the present invention has the advantages of high strength, good thermal shock stability, good corrosion resistance, etc., and is suitable for high-tech crematorium.
[0026] (2) The present invention uses ferromanganese alloy and alumina as raw materials and performs high-temperature sintering under carbon-buried atmosphere conditions, so that the ferromanganese alloy, alumina and CO in the atmosphere undergo a gas-liquid-solid reaction to generate a composite spinel-corundum refractory material having manganese-aluminum spinel and iron-aluminum spinel reinforcement phases. Manganese-aluminum spinel has a high melting point, a low thermal expansion coefficient and good structural flexibility; iron-aluminum spinel has excellent resistance to erosion by alkaline media. Therefore, the composite spinel-corundum refractory material prepared by the present invention has the excellent properties of both manganese-aluminum spinel and iron-aluminum spinel, and can overcome the problems of unsatisfactory performance and short service life of clay and high-aluminum refractory materials for crematoriums in the prior art.
[0027] (3) The present invention uses ferromanganese alloy as the manganese source / iron source for in-situ synthesis, which can achieve the regulation of the oxygen partial pressure inside the material, so that Mn 2+ and Fe 2+ The ions exist stably and their valence change is suppressed, thus effectively promoting the efficient synthesis of manganese aluminum spinel and iron aluminum spinel.
[0028] (4) The preparation method (firing process) of the present invention is controllable, has high production efficiency, is suitable for industrial production, and has a high product qualification rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 It is a schematic diagram of the preparation process of the corundum-manganese aluminum spinel-iron aluminum spinel composite refractory material of the present invention;
[0031] Figure 2 This is the binary phase diagram of Mn-Fe. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] The schematic diagram of the preparation process of the corundum-manganese aluminum spinel-iron aluminum spinel composite refractory material of the present invention is shown in Figure 1 .
[0038] The composition of the ferromanganese alloy used in the present invention is 65wt.% Mn and 35wt.% Fe.
[0039] Example 1
[0040] A method for preparing a composite spinel-corundum refractory material for a crematorium:
[0041] (1) The composite spinel-corundum refractory material for crematorium is composed of the following raw materials, measured by mass percentage: 95wt.% of alumina and 5wt.% of ferromanganese alloy.
[0042] The alumina is composed of 70 wt.% alumina aggregate and 30 wt.% active alumina powder (particle size ≤ 45 μm); and the particle size of the ferromanganese alloy is ≤ 100 μm.
[0043] The alumina aggregate is composed of alumina with a particle size of 1 mm < ≤ 3 mm and a particle size of 0 < ≤ 1 mm in a mass ratio of 55:15.
[0044] (2) Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm × 125 mm × 200 mm).
[0045] (3) Dry the bricks (temperature is 50°C, time is 48h) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1650°C for 5h (high temperature firing) to obtain composite spinel-corundum refractory materials (corundum-manganese aluminum spinel-iron aluminum spinel composite refractory materials) for crematoriums.
[0046] The composite spinel-corundum refractory material for crematorium prepared in this embodiment has a room temperature compressive strength of 141 MPa, a thermal shock stability (1100° C., water cooling) of ≥30 times, and a first-class alkali resistance according to GB / T 14983-2008 standard test.
[0047] Example 2
[0048] A method for preparing a composite spinel-corundum refractory material for a crematorium:
[0049] (1) The composite spinel-corundum refractory material for crematorium is composed of the following raw materials, measured by mass percentage: 93wt.% of alumina and 7wt.% of ferromanganese alloy.
[0050] The alumina is composed of 70 wt.% alumina aggregate and 30 wt.% active alumina powder (particle size ≤ 45 μm); and the particle size of the ferromanganese alloy is ≤ 100 μm.
[0051] The alumina aggregate is composed of alumina with a particle size of 1 mm < ≤ 3 mm and a particle size of 0 < ≤ 1 mm in a mass ratio of 55:11.
[0052] (2) Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm × 125 mm × 200 mm).
[0053] (3) Dry the bricks (temperature is 150°C, time is 24h) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1650°C for 10h (high temperature firing) to obtain composite spinel-corundum refractory materials for crematoriums.
[0054] The composite spinel-corundum refractory material for crematorium prepared in this embodiment has a room temperature compressive strength of 211 MPa, a thermal shock stability (1100° C., water cooling) of ≥40 times, and a first-class alkali resistance according to GB / T 14983-2008 standard test.
[0055] Example 3
[0056] A method for preparing a composite spinel-corundum refractory material for a crematorium:
[0057] (1) The composite spinel-corundum refractory material for crematorium is composed of the following raw materials, measured by mass percentage: 88wt.% of alumina and 12wt.% of ferromanganese alloy.
[0058] The alumina is composed of 70 wt.% alumina aggregate and 30 wt.% active alumina powder (particle size ≤ 45 μm); and the particle size of the ferromanganese alloy is ≤ 100 μm.
[0059] The alumina aggregate is composed of alumina with a particle size of 1 mm < ≤ 3 mm and alumina with a particle size of 0 mm < ≤ 1 mm in a mass ratio of 55:15.
[0060] (2) Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm × 125 mm × 200 mm).
[0061] (3) Dry the bricks (temperature is 150°C, time is 10 hours) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1700°C for 12 hours (high temperature firing) to obtain composite spinel-corundum refractory materials for crematoriums.
[0062] The composite spinel-corundum refractory material for crematorium prepared in this embodiment has a room temperature compressive strength of 249 MPa, a thermal shock stability (1100° C., water cooling) of ≥40 times, and a first-class alkali resistance according to GB / T 14983-2008 standard test.
[0063] Example 4
[0064] A method for preparing a composite spinel-corundum refractory material for a crematorium:
[0065] (1) The composite spinel-corundum refractory material for crematorium is composed of the following raw materials, measured by mass percentage: 80wt.% of alumina and 20wt.% of ferromanganese alloy.
[0066] The alumina is composed of 65wt.% alumina aggregate and 35wt.% active alumina powder (particle size ≤ 45μm); the particle size of the ferromanganese alloy is ≤ 100μm.
[0067] The alumina aggregate is composed of alumina with a particle size of 1 mm < ≤ 3 mm and a particle size of 0 < ≤ 1 mm in a mass ratio of 50:15.
[0068] (2) Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm × 125 mm × 200 mm).
[0069] (3) Dry the bricks (temperature is 100°C, time is 35 hours) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1600°C for 15 hours (high temperature firing) to obtain composite spinel-corundum refractory materials for crematoriums.
[0070] The composite spinel-corundum refractory material for crematorium prepared in this embodiment has a room temperature compressive strength of 212 MPa, a thermal shock stability (1100° C., water cooling) of ≥40 times, and a first-class alkali resistance according to GB / T 14983-2008 standard test.
[0071] Example 5
[0072] A method for preparing a composite spinel-corundum refractory material for a crematorium:
[0073] (1) The composite spinel-corundum refractory material for crematorium is composed of the following raw materials, measured by mass percentage: 85wt.% of alumina and 15wt.% of ferromanganese alloy.
[0074] The alumina is composed of 55wt.% alumina aggregate and 45wt.% active alumina powder (particle size ≤ 45μm); the particle size of the ferromanganese alloy is ≤ 100μm.
[0075] The alumina aggregate is composed of alumina with a particle size of 1 mm < 3 mm and a particle size of 0 < 1 mm in a mass ratio of 50:5.
[0076] (2) Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm × 125 mm × 200 mm).
[0077] (3) Dry the bricks (temperature is 120°C, time is 24h) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1700°C for 15h (high temperature firing) to obtain composite spinel-corundum refractory materials for crematoriums.
[0078] The composite spinel-corundum refractory material for crematorium prepared in this embodiment has a room temperature compressive strength of 228 MPa, a thermal shock stability (1100° C., water cooling) of ≥40 times, and a first-class alkali resistance according to GB / T 14983-2008 standard test.
[0079] Comparative Example 1
[0080] Preparation method of refractory materials:
[0081] (1) The refractory material is composed of the following raw materials, by mass percentage: a mixed fine powder of 85 wt.% of alumina, 9 wt.% of MnO and 6 wt.% of FeO, wherein the particle size of the mixed fine powder is ≤45 μm.
[0082] The alumina is composed of 65wt.% of alumina aggregate and 35wt.% of activated alumina powder (particle size ≤ 45μm).
[0083] The alumina aggregate is composed of alumina with a particle size of 1 mm < ≤ 3 mm and a particle size of 0 < ≤ 1 mm in a mass ratio of 50:15.
[0084] (2) Alumina and mixed fine powders of MnO and FeO are kneaded uniformly and then pressed into shape to obtain a brick (size: 65 mm×125 mm×200 mm).
[0085] (3) Dry the bricks (temperature of 50-150°C, time of 10-48h) until the residual moisture is less than 1.5wt.%, and then place them in a tunnel kiln and keep them at 1700°C for 15h (high temperature firing) to obtain refractory materials for crematoriums.
[0086] The room temperature compressive strength of the refractory material prepared in this comparative example is 102 MPa, the thermal shock stability (1100° C., water cooling) is 18 times, and the alkali resistance of the material tested according to GB / T 14983-2008 standard is level 2.
[0087] Comparative Example 1 uses MnO and FeO oxides as manganese and iron sources. During the high-temperature sintering process, part of MnO and FeO react with Al2O3 to form a small amount of manganese-aluminum spinel and iron-aluminum spinel. However, the low oxygen partial pressure condition inside the material is unstable, and most of MnO and FeO undergo oxidation reaction to form MnO2 and Fe2O3, and spinel cannot be formed; the Mn in the generated manganese-aluminum spinel and iron-aluminum spinel is 2+ , Fe 2+ A change in valence occurs, accompanied by a large volume expansion, which causes the bonds between the particles to be destroyed. The material strength is low, only 102MPa, the thermal shock stability (1100°C, water cooling) is only 18 times, and the alkali resistance is level two.
[0088] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A composite spinel-corundum refractory material for a cremator, characterized in that: The raw materials include, by mass percentage, 80-95% of aluminum oxide and 5-20% of ferromanganese alloy; The preparation method of the composite spinel-corundum refractory material for a cremator comprises the following steps: Alumina and ferromanganese alloy are mixed and kneaded uniformly and then pressed into shape to obtain a brick blank; The bricks are dried and then fired at high temperature to obtain the composite spinel-corundum refractory material for the crematorium; The high temperature sintering is carried out under the condition of air-carbon buried atmosphere; The high temperature sintering temperature is 1600-1750° C. and the time is 5-15 hours.
2. The composite spinel-corundum refractory material for crematorium according to claim 1, characterized in that: The alumina is composed of alumina aggregate and activated alumina powder; the particle size of the alumina aggregate is greater than 0 mm and less than or equal to 3 mm.
3. The composite spinel-corundum refractory material for crematorium according to claim 2, characterized in that: In terms of mass percentage, the alumina aggregate accounts for 55-70%, and the activated alumina powder accounts for 30-45%.
4. The composite spinel-corundum refractory material for crematorium according to claim 1, characterized in that: The particle size of the ferromanganese alloy is ≤100 μm.
5. The composite spinel-corundum refractory material for crematorium according to claim 1, characterized in that: The drying specifically includes: drying until the residual moisture of the brick is less than 1.5wt.%; the drying temperature is 50-150°C.
6. Use of the composite spinel-corundum refractory material for crematorium according to any one of claims 1 to 5 in the preparation of crematorium.
Citation Information
Patent Citations
Al2O3-MgO fire-resistant material pouring casting material and preparation thereof
CN101462886A
Method for improving slag permeation resistance of refractory aluminum-chromium material
CN105330314A